Pengaruh Jumlah Produksi, Tenaga Kerja dan Kurs Valuta Asing Terhadap Ekspor Perhiasan Perak di Kabupaten Gianyar - Lestari, Kadek Julia; Wirathi, I G A P (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
The economy of a country is not regardless of a country's international trade relations with other countries, including through export activities either in the form of goods or services produced. Bali especially in Gianyar Regency has considerable export potential in the export of silver jewelry because of its artistry and unique customs then became the attraction on behalf of consumer. The purpose of this research is to analyze the effect of the amount of production, labor, and the foreign exchange rates against the exports of silver jewelry in Gianyar Bali simultaneous and partial. In addition to knowing the variables which effect is dominant against the export of silver in Gianyar Regency of Bali. The study using secondary data from 2012-2015 are collected from the Department of industry and trade of the Gianyar Regency. This research used multiple linear analysis. The results showed that the number of positive and influential production significantly to exports of silver jewelry in the Gianyar Regency. Meanwhile, labor and foreign exchange rate has no effect against the exports of silver jewelry in the Gianyar Regency. The amount of production is the dominant against the influential varibel export in the Gianyar Regency.
Keywords: export amount of silver jewelry; production; labor; foreign currency exchange rate